2019
DOI: 10.3389/fcell.2019.00169
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Understanding the Reversal of Gene Silencing During X Chromosome Reactivation

Abstract: Dosage compensation between XX female and XY male cells is achieved by a process known as X chromosome inactivation (XCI) in mammals. XCI is initiated early during development in female cells and is subsequently stably maintained in most somatic cells. Despite its stability, the robust transcriptional silencing of XCI is reversible, in the embryo and also in a number of reprogramming settings. Although XCI has been intensively studied, the dynamics, factors, and mechanisms of X chromosome reactivation (XCR) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 143 publications
(236 reference statements)
0
14
0
Order By: Relevance
“…During this process, Xist repels architectural proteins like CTCF and Cohesin (Minajigi et al, 2015), thereby actively contributing to the attenuation of TADs (Wang et al, 2018) and leading to he Xi di inc chromo ome conforma ion (Colognori et al, 2019;Giorgetti et al, 2016;Splinter et al, 2011). There has been intense research effort to understand the dynamics of transcriptional silencing, the mechanisms of transition to the unique structure of the Xi and the connection between the two processes (Froberg et al, 2018;Gdula et al, 2019;Wang et al, 2018Wang et al, , 2019, but how the process is reversed during the reactivation of the X chromosome has received attention only recently (Cantone and Fisher, 2017;Payer, 2016;Talon et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…During this process, Xist repels architectural proteins like CTCF and Cohesin (Minajigi et al, 2015), thereby actively contributing to the attenuation of TADs (Wang et al, 2018) and leading to he Xi di inc chromo ome conforma ion (Colognori et al, 2019;Giorgetti et al, 2016;Splinter et al, 2011). There has been intense research effort to understand the dynamics of transcriptional silencing, the mechanisms of transition to the unique structure of the Xi and the connection between the two processes (Froberg et al, 2018;Gdula et al, 2019;Wang et al, 2018Wang et al, , 2019, but how the process is reversed during the reactivation of the X chromosome has received attention only recently (Cantone and Fisher, 2017;Payer, 2016;Talon et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…During this process, Xist repels architectural proteins like CTCF and Cohesin 11 , thereby actively contributing to the attenuation of TADs 8 and leading to the distinct chromosome conformation 7,17,18 of the Xi. There has been intense research effort to understand the dynamics of transcriptional silencing, the mechanisms of transition to the unique structure of the Xi and the connection between the two processes 8,9,19,20 , but how the process is reversed during the reactivation of the X chromosome has received attention only recently 1,21,22 .…”
mentioning
confidence: 99%
“…Despite its importance, much less is known about XCR compared with XCI. In contrast to XCI, XCR leads to the silencing of Xist, increased expression of antisense lncRNA Tsix, loss of repressive chromatin marks, recruitment of active chromatin modifications, and subsequent chromosomewide gene reactivation (Pasque and Plath 2015;Talon et al 2019). Previous studies during mouse development have shown that the reversal of iXCI is a gradual process over 24 h. XCR initiates before the loss of Xist and is partially restricted by H3K27me3, which is actively removed by KDM6A (also known as UTX) H3K27 histone demethylase in order to activate slowly reactivating genes (Borensztein et al 2017a).…”
mentioning
confidence: 99%